Desensitisation to cigarette package graphic health warnings: a cohort comparison between London and Singapore. Issue 10 (24th October 2016) - Ratneswaran, Culadeeban; Chisnall, Ben; Li, Mingyue; Tan, Sarah; Douiri, Abdel; Anantham, Devanand; Steier, Joerg
Abstract : Objectives: We compared 2 sociocultural cohorts with different duration of exposure to graphic health warning labels (GHWL), to investigate a possible desensitisation to their use. We further studied how a differing awareness and emotional impact of smoking-associated risks could be used to prevent this. Setting: Structured interviews of patients from the general respiratory department were undertaken between 2012 and 2013 in 2 tertiary hospitals in Singapore and London. Participants: 266 participants were studied, 163 Londoners (35% smokers, 54% male, age 52±18 years) and 103 Singaporeans (53% smokers, p=0.003; 78% male, p<0.001; age 58±15 years, p=0.012). Main outcomes and measures: 50 items assessed demographics, smoking history, knowledge and the deterring impact of smoking-associated risks. After showing 10 GHWL, the impact on emotional response, cognitive processing and intended smoking behaviour was recorded. Results: Singaporeans scored lower than the Londoners across all label processing constructs, and this was consistent for the smoking and non-smoking groups. Londoners experienced more 'disgust' and felt GHWL were more effective at preventing initiation of, or quitting, smoking. Singaporeans had a lower awareness of lung cancer (82% vs 96%, p<0.001), despite ranking it as the most deterring consequence of smoking. Overall, 'blindness' was the least known potential risk (28%), despite being ranked as more deterring than 'stroke' and 'oral cancer' in all participants. Conclusions: The length of exposure to GHWL impacts on the effectiveness. However, acknowledging the different levels of awareness and emotional impact of smoking-associated risks within different sociocultural cohorts could be used to maintain their impact.